The First Woman Yamī, Her Origin and Her Status in Indo-Iranian Mythology: Demigoddess or Half-human? (Evidence from R̥gveda 10.10, Iranian Parallels and Greek Relatives) - Kulikov, Leonid (Studia Ceranea, 2018)
This paper focuses on the mythology of Yamī and her twin-brother Yama (the first humans according to Indo-Iranian mythology), their non-human origin and some aspects of Yamī’s behaviour which presumably betray a number of features of a female half-deity. The relationships between Yamī and Yama are the central topic of the dialogue hymn Rgveda 10.10, where Yamī attempts to seduce her twin to incest in order to produce offspring and thus continue the human race. This offer is refused by Yama, who refers to the inappropriateness of incest. Although Yamī and Yama are humans according to the Vedic tradition, their origin from two half-deities – a Gandharva father and an Apsara mother – remains inexplicable: how could a couple of non-human beings (half-deities or demons) give birth to humans? Obviously, the mythological status of the twins should be reconsidered. I argue that at least one of them, Yamī, retains immortality and some other features of the non-human (semi-divine) nature. On the basis of the analysis of the Yama and Yamī hymn and some related Vedic texts, I argue that this assumption may account for certain peculiarities of Yamī’s behaviour – particularly her hypersexuality (which can be qualified as demonic type of behaviour), as opposed to the much more constrained, human type of conduct displayed by Yama. Given the notoriously lustful character of the Gandharvas, an origin from this semi-divine creature may account for Yamī’s hypersexuality. Although the word gandharvá- does not have Indo-European etymology, we can find possible Indo-European parallels. In particular, the Gandharvas are comparable with the Centaurs, which cannot be etymologically related but possibly originate in the same non-Indo-European source. There are some reasons to assume that both words are borrowed from the Kassite language and mythology, which, in turn, may have been related to the language and culture of the Proto-North-Caucasians. Although we do not find exact equivalents of Yamī outside of the Indo-Iranian pantheon, indirect parallels can be found in other Indo-European traditions. The Apsaras (water nymphs) can be compared to a variety of water deities (nymphs) in Greek mythology, such as the Naiads, or to the Slavic rusalki.